Synthesis of Graphene Oxide Nanoparticles by Laser Ablation System - Jeryo, Atiaf K.; Abbas, Qusay Adnan (Iraqi Journal of Science, 2020)
In this study, graphene oxide (GO) and reduced graphene oxide were synthesized by pulsed Nd:YAG laser with a fundamental wavelength (1064 nm) focused on the pure graphite target which was immersed in distilled water. Different pulse energies were applied in two cases; with and without magnetic field. The synthesized GO and rGO nanoparticles were characterized by UV-visible spectroscopy, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and atomic force microscopy (AFM) with and without magnetic field. The data show the presence of a magnetic field which illustrated increasing oxygen functional groups of GO. This caused a change in the morphology of the surface of GO, increasing crystallite size from 12.19 nm to 71.2 nm. The interlayer distance (d-space) was reduced from 0.4 nm to 0.25 nm and the absorption peaks that appeared in the spectrum were reduced and shifted toward smallest wavelengths, while the stretching vibration of the O-H group peak was shifted toward largest wavelengths.